38 year old male complaining of “seeing spots” OS - Roth, Daniel (Digital Journal of Ophthalmology, 1997)
A 38 year old Hispanic male with AIDS presents to the Bascom Palmer Eye Institute complaining of “seeing spots” OS. He notes that his last CD4 count was 20 in September 1995. His past ocular history was notable for trauma to OD in 1984 with corneal perforation and traumatic cataract formation. He underwent primary repair of the corneal laceration and cataract extraction. He was left aphakic OD after the procedure.